2010
DOI: 10.1111/j.1462-5822.2010.01434.x
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum stress is induced and modulated by enterovirus 71

Abstract: SummaryPicornavirus infection alters the endoplasmic reticulum (ER) membrane but it is unclear whether this induces ER stress. Infection of rhabdomyosarcoma cells with enterovirus 71 (EV71), a picornavirus, caused overexpression of the ER-resident chaperone proteins, BiP and calreticulin, and phosphorylation of eIF2a, but infection with UV-inactivated virus did not, indicating that ER stress was induced by viral replication and not by viral attachment or entry. Silencing (si)RNA knockdown demonstrated that pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
70
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 70 publications
(181 reference statements)
8
70
0
Order By: Relevance
“…40,41,49,50 Viruses exploit the translational machinery of the host cell to synthesize their viral proteins, leading to increased folding pressure on the ER and chaperone upregulation. 51,52 Thus, it is likely that the adaptive and proapoptotic pathways of UPR are involved in the pathophysiology of viral myocarditis. Furthermore, Mao et al demonstrated that ER stress plays an important role in cardiomyocyte apoptosis and the development of dilated cardiomyopathy in rabbits immunized with a peptide corresponding to the ␤1-aderenoceptor.…”
Section: Cardiac Hypertrophy and Failurementioning
confidence: 99%
“…40,41,49,50 Viruses exploit the translational machinery of the host cell to synthesize their viral proteins, leading to increased folding pressure on the ER and chaperone upregulation. 51,52 Thus, it is likely that the adaptive and proapoptotic pathways of UPR are involved in the pathophysiology of viral myocarditis. Furthermore, Mao et al demonstrated that ER stress plays an important role in cardiomyocyte apoptosis and the development of dilated cardiomyopathy in rabbits immunized with a peptide corresponding to the ␤1-aderenoceptor.…”
Section: Cardiac Hypertrophy and Failurementioning
confidence: 99%
“…Because many picornaviruses can induce ER stress [29, 30] and this ER stress induces autophagy [3133], EMCV might cause ER stress and therefore induce autophagy. To test this hypothesis, we analyzed whether the marker molecules of the ER stress were regulated in BHK-21 cells by EMCV infection, 2C or 3D protein expression or thapsigargin (Tg) treatment (as a positive control), which is a known ER stress inducer [34].…”
Section: Resultsmentioning
confidence: 99%
“…Although studies showed that many picornaviruses induce autophagy by activating ER stress [29, 30], a question remains as to whether the underlying mechanisms of EMCV and 2C or 3D protein-induced autophagy are related to ER stress. Thus, the activation of the ER stress pathway was analyzed in BHK-21 cells infected with EMCV, expressed 2C or 3D protein or treated with Tg (as a positive control) (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coxackievirus A9 infection of permissive cells requires GRP78 and major histocompatibility complex class I molecules, which are essential for virus internalization (25). It has been reported that the expression of GRP78 is activated by an enterovirus 71-dependent mechanism and that enterovirus 71 infection induces ER stress, but modifies the outcome to assist viral replication (26). …”
Section: Methodsmentioning
confidence: 99%